2018
DOI: 10.14260/jemds/2018/326
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Factors on Foetal Malnutrition Using Can Score Assessment- A Tertiary Care Centre Experience

Abstract: BACKGROUND Potential conditions that predispose babies to being small at birth are quite common in tropical practice. Several factors may predispose to SGA delivery. 1 Maternal factors known to contribute to foetal malnutrition (FM) include biological factors, nutritional factors, brief interpregnancy intervals, low socioeconomic class, poor education, medical and obstetric problems. The main aim of the study was to assess whether maternal factors are influencing the nutritional status of foetus. MATERIALS AND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…On the contrary, a study done by Ajay Mohan et al, used a modified CAN score cut off < 21, as more babies were clustered between 21 and 24 in their cohort. 19 To classify nutritional status of new born, PI has been used by various investigators. 15,20 PI relies on the principle that length is spared at the expense of weight during acute conditions; whereas, weight and length both are proportionately impaired in chronic insults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, a study done by Ajay Mohan et al, used a modified CAN score cut off < 21, as more babies were clustered between 21 and 24 in their cohort. 19 To classify nutritional status of new born, PI has been used by various investigators. 15,20 PI relies on the principle that length is spared at the expense of weight during acute conditions; whereas, weight and length both are proportionately impaired in chronic insults.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by many investigators. 3,[10][11][12]19 A study done by Soundarya M et al, concluded that FM is best identified by CAN score and BMI is best screening tool for FM and when coupled with PI will identify most normally nourished newborns. 21 Application of weight standard alone may be inappropriate in studying nutritional status in many diverse and multi-ethnic population groups.…”
Section: Discussionmentioning
confidence: 99%